Pomen permanentnega izobraževanja v zdravstveni negi - Hoyer, Silvestra (Obzornik zdravstvene nege, 2004)
The article deals with education in nursing care in the light of permanent life-time learning. Some characteristics and the importance of adult educationare stressed. Lately, the profession of nursing and nursing care itself are developing intensively. Therefore, social acceptance, better identification of carriers of the profession, also through knowledge, solid positions and values of the profession is required.
Keywords: education; Education, Nursing, Continuing; izobraževanje; Izobraževanje, zdravstvena nega nadaljevalno; medicinske sestre; zdravstvena nega